PENGEMBANGAN PEMASARAN KOPI BUBUK LIBERIKA MERANTI DI DESA KEDABU RAPAT KECAMATAN RANGSANG PESISIR KABUPATEN KEPULAUAN MERANTI (KASUS PADA CV. ZAROHA) - Septi Veronica; Sri Ayu Kurniati (UIR Press, 2022)
Meranti Islands Regency has the potential to develop Liberian coffee. It is important to develop marketing to increase profits. The purpose of this study is to analyze: (1) the business profile, (2) ground coffee processing techniques (3) internal and external environment affecting marketing, (4) marketing strategy, and (5) marketing strategy priority. The research method is a case study of Liberika Meranti Ground Coffee Processing Company CV Zaroha in Meranti Islands Regency, Rangsang Pesir District, Kedabu Meeting Village, from January to May 2021. The respondents consisted of 4 employees, including contractors. Research data comes from primary data and secondary data. The data was analysed using SWOT and QSPM methods. The results showed that CV. Zaroha was established in 2008 and is classified as a small-scale business with a capital of Rp. 63.813.00. The fraw materials used are an average of 20 tons/month with a price of Rp. 3,500/kg and the worker comes from outside the family. Liberika coffee processing techniques into ground coffee through various processes, starting from weighing, pulling, fermentation, drying, hulling, roasting, grading, and packing. Having a business license and trademark is one of the advantages, but the lack of online-based promotions and higher prices than other coffees are weaknesses for CV. Zaroha. The SWOT matrix showed that the business was in the SO (Strength and Opportunities) quadrant with a strategy of utilizing online media in increasing marketing, adding sales outlets with varied products, becoming a supplier for Coffee Shops as well as fulfilling and standardizing export requirements so that the market share become bigger.